REVIEW ON CONVENTIONAL CONCRETE AND NYLON FIBER REINFORCED CONCRETE BEHAVIOR (Malaysian Journal of Civil Engineering, 2023)
The addition of fibers to reinforced cement concrete enhances the suitability of structures under impacts and earthquake loads by boosting firmness or energy-consuming proficiency of the hardened concrete material. During cracking of concrete, one of the most relevant behaviors of fiber like “bridge effect” starts functioning. As a result of this, fiber blocks crack formation and propagation, and hence strength and ductility of concrete structure improve. The goal of this study is to compare the mechanical properties of reinforced cement concrete by mixing nylon fibers and without mixing nylon fibers. In this study, data from existing article are assessed to compare the strengths of nylon fiber reinforced concrete and conventional concrete by using concrete strength measuring test results such as compressive strength test, flexural strength test, and split tensile strength test. Adding fiber with concrete mix reduces the moisture content, thereby lessening the workability of concrete which produces ﬁber ball. Due to the obvious lack of homogeneity caused by fiber balling, the efficiency of fiber reinforced concrete is reduced. During the mixing of small portions of fibers with dry concrete the difficulty of fiber separation can prevent by providing good distribution and scattering within the mixtures which enhance concrete strength and thus the balling incident can escape. The dynamic transmission of stress between concrete mix and the fiber achieves by considering significant factors like aspect ratio, volume, and orientation of the fiber. Nylon fiber provides mechanical improvement of reinforced concrete by enhancing impact resistance and increasing flexural toughness, as a result the load-bearing capacity of concrete develops effectively. Introducing nylon fibers with concrete mixture promotes strong tensile comportment of concrete outstandingly after the post peak stage.